Impact of anticoagulation on recurrent thrombosis and bleeding after hematopoietic cell transplantation. Issue 9 (24th June 2021) - Martens, Kylee L.; Amos, Christopher I.; Hernandez, Cristhiam Rojas; Kebriaei, Partow; da Costa, Wilson L.; Basom, Ryan; Davis, Chris; Kesten, Madeline; Carrier, Marc; Garcia, David A.; Lee, Stephanie J.; Li, Ang
Abstract: History of venous thromboembolism (VTE) is prevalent among patients undergoing hematopoietic cell transplantation (HCT). Management of anticoagulation is particularly challenging as most patients will have chemotherapy‐induced thrombocytopenia while awaiting engraftment post‐HCT. We conducted a retrospective study of autologous and allogeneic HCT recipients with prior VTE from 2006–2015 to 1) compare anticoagulant strategies on short‐term VTE recurrence and bleeding and 2) assess predictors for VTE recurrence beyond 30 days. Patients with VTE were allocated to two cohorts based on anticoagulant strategy at thrombocytopenia onset and underwent inverse probability weighting to assess primary outcomes of VTE recurrence and bleeding within 30 days post‐HCT. Subsequently, multivariable logistic regression model was used to assess the association of 100‐day VTE recurrence by the HIGH‐2‐LOW VTE risk assessment score and whether patients resumed anticoagulation at platelet recovery. Thirteen percent of recipients had VTE prior to HCT; of those meeting inclusion criteria, 227 continued anticoagulation and 113 temporarily discontinued it. Anticoagulant strategy was not significantly associated with decreased risk of VTE recurrence within 30 days (3% vs 4%, p  = 0.61); however, risk of overall bleeding was non‐significantly higher in those who continued vs discontinued anticoagulation (41% vs 31%, p  = 0.08). In a subgroup of 250 allogeneic HCT patients, every one‐point increase of HIGH‐2‐LOW score was significantly associated with VTE recurrence at 100 days (OR 1.57 [95% CI 1.10–2.23]), while anticoagulation resumption upon platelet engraftment was associated with lower recurrent risk (OR 0.48 [0.20–1.14]). Temporarily withholding anticoagulation during thrombocytopenia may optimize risk–benefit tradeoffs, though additional strategies are essential to prevent VTE recurrence after hematopoietic recovery.